Vacuum heat insulating material
The vacuum insulation material, featuring a core with fumed silica, radiation inhibitors, and glass fibers with controlled sodium and potassium content, addresses the issue of moisture-induced thermal conductivity decline in conventional materials, achieving improved long-term reliability and insulation performance.
Patent Information
- Application Number
- JP2023167542
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Conventional vacuum insulation materials suffer from deterioration in thermal conductivity due to moisture ingress through the heat-fused portions of the outer bag, leading to a decline in insulation performance over time.
A vacuum insulation material comprising a core material with fumed silica, radiation inhibiting components, and glass fibers, where the glass fibers have a sodium and potassium oxide content ratio of 11% by mass or less, and the alkaline elution amount is 1.9 mL/g or less, is used. This material is enclosed in a gas barrier film outer bag, which maintains a reduced pressure environment.
The proposed vacuum insulation material effectively suppresses the deterioration of thermal conductivity due to moisture ingress, thereby enhancing long-term reliability and maintaining excellent insulation performance.
Smart Images

Figure 2025057793000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a vacuum insulation material. [Background technology]
[0002] Vacuum insulation materials are used in various fields such as refrigerators and water heaters. A known example of a vacuum insulation material is a vacuum insulation material in which a molded body made of a core material containing powder and glass fiber is vacuum sealed in an outer bag (Patent Document 1). Although vacuum insulation materials using powder as the core material have inferior initial insulation performance compared to vacuum insulation materials using only fibers such as glass fiber as the core material, they are excellent in durability because they can maintain sufficient insulation performance even in a low vacuum. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-215538 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, conventional vacuum insulation materials such as those described in Patent Document 1 have a problem in that moisture gradually seeps into the interior through the heat-sealed parts of the outer bag that seals the core material under reduced pressure, causing the thermal conductivity to deteriorate and the insulation performance to gradually decrease.
[0005] An object of the present invention is to provide a vacuum insulation material that can suppress deterioration of thermal conductivity due to moisture penetrating into the interior and has excellent long-term reliability. [Means for solving the problem]
[0006] The present invention includes the following configurations. [1] A vacuum insulation material comprising a core material and a gas barrier film covering the core material, the core material being vacuum sealed in an outer bag formed of the gas barrier film, the core material comprises fumed silica, a radiation suppressing component, and glass fibers; A vacuum insulation material, in which the ratio of the combined mass of Na2O and K2O contained in the glass fibers to the total mass of the glass fibers is 11 mass% or less. [2] The vacuum insulation material according to [1], wherein the amount of alkali elution from the glass fiber is 1.9 mL / g or less. [3] The thermal expansion coefficient of the glass fiber is 90×10 -7 / °C or less. [4] The vacuum insulation material according to any one of [1] to [3], wherein the glass fiber has a Young's modulus of 50 GPa or more. [5] The vacuum insulation material according to any one of [1] to [4], wherein the glass constituting the glass fibers is at least one type selected from aluminoborosilicate glass, borosilicate glass, and aluminosilicate glass. [6] The content ratio of the fumed silica is 50 to 90 mass%, the content ratio of the radiation suppression component is 3 to 30 mass%, and the content ratio of the glass fiber is 2 to 30 mass%, relative to the total mass of the core material; The density of the core material sealed under reduced pressure is 0.30 g / cm 3 is as follows: The fiber length of the glass fiber is in the range of 0.1 to 10 mm. The vacuum insulation material according to any one of [1] to [5], wherein a fiber length distribution Lw / Ln represented by a ratio of the number average fiber length Ln to the weight average fiber length Lw of the glass fibers is 1.05 or more. [7] The vacuum insulation material described in [6], wherein the fiber length D10 of the glass fiber is 2.4 mm or less. [8] The vacuum insulation material according to [6] or [7], wherein the fiber length spread index (D90-D10) / D50 of the glass fiber, expressed as the difference between the fiber length D90 and the fiber length D10 relative to the fiber length D50 of the glass fiber, is 0.21 or more. [9] The vacuum insulation material according to any one of [6] to [8], wherein the radiation suppression component is one or more selected from graphite, silicon carbide, titanium oxide, tin oxide, and potassium titanate.
[10] A vacuum insulation material according to any one of [6] to [9], which is produced as a flat vacuum insulation material and has a distortion of 0.25% or less when a pressure of 4400 Pa is applied to a plane in the thickness direction of the vacuum insulation material for one hour. Effect of the Invention
[0007] According to the present invention, there is provided a vacuum insulation material that is excellent in long-term reliability and can suppress deterioration of thermal conductivity due to moisture penetrating into the interior. [Brief description of the drawings]
[0008] [Figure 1] 1 is a cross-sectional view showing a schematic configuration of a vacuum insulation material according to an embodiment. [Diagram 2] 1 is a graph showing frequency distribution based on the number of fibers versus fiber length (mm) for Fiber 6 used in Example 6 and Fiber 8 used in Example 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The following terms have the following meanings: The term "core material" refers to a molded body made of a raw material mixture in a vacuum insulation material, which is molded into a desired shape. The term "fumed silica" refers to fine silica particles consisting of amorphous, spherical, pore-free primary particles. Fumed silica can be obtained, for example, by vaporizing silicon tetrachloride and carrying out a gas-phase reaction in a high-temperature hydrogen flame. The term "radiation suppression component" refers to particles that suppress radiative heat transfer by reflecting or scattering infrared light, or by absorbing infrared light and then isotropically radiating the amount of the temperature increase caused by the absorption, thereby disrupting the directionality of the infrared light. "Average aggregate particle diameter D50 of fumed silica" is the volume-based cumulative 50% diameter of fumed silica determined by laser diffraction scattering. In other words, in the volume-based frequency particle size distribution of fumed silica determined by laser diffraction scattering, a cumulative curve is obtained with the total volume of the particle group as 100%, and the particle diameter at the point on the cumulative curve where the cumulative volume is 50% is defined as D50. "Glass fiber length D10" means the fiber length at the point where the cumulative number is 10% in the cumulative number distribution curve where the total number of fibers in the fiber length distribution calculated by number is 100%. "Fiber length D50" means the fiber length at the point where the cumulative number is 50% in the cumulative number distribution curve where the total number of fibers in the fiber length distribution calculated by number is 100%. "Fiber length D90" means the fiber length at the point where the cumulative number is 90% in the cumulative number distribution curve where the total number of fibers in the fiber length distribution calculated by number is 100%. The fiber length distribution is determined by the frequency distribution and cumulative number distribution curve obtained by measuring the lengths of 50 or more fibers randomly in a photograph observed with an optical microscope. A numerical range expressed using "~" includes the numerical values on either side of the "~" within the numerical range.
[0010] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to the embodiment described below, and various modifications are possible without departing from the gist of the present invention.
[0011] [Vacuum insulation material] A vacuum insulation material according to an embodiment of the present invention comprises a core material and a gas barrier film covering the core material, and the core material is vacuum sealed in an outer bag formed of the gas barrier film, the core material containing fumed silica, a radiation suppression component, and glass fibers, and the ratio of the combined mass of Na2O and K2O contained in the glass fibers to the total mass of the glass fibers (hereinafter also referred to as "ratio A") is 11 mass% or less.
[0012] Fig. 1 is a cross-sectional view showing a vacuum insulation material 1 according to an embodiment. Note that the dimensions and the like shown in the drawings in the following description are merely examples, and the present invention is not necessarily limited thereto, and can be appropriately modified and implemented without departing from the gist of the present invention.
[0013] The vacuum insulation material 1 comprises a core material 10 and an outer bag 12, and the core material 10 is sealed in the outer bag 12 under reduced pressure. For example, the core material 10 is housed in an outer bag 12 made by forming a gas barrier film into a bag shape, and the opening of the outer bag 12 is sealed under reduced pressure to obtain the vacuum insulation material 1.
[0014] (Core material) The vacuum insulation material according to the embodiment uses glass fibers with a ratio A of 11% by mass or less in the core material, which prevents the thermal conductivity from gradually decreasing due to moisture penetrating into the vacuum insulation material, improving long-term reliability. The mechanism by which such an effect is obtained is not necessarily clear, but is thought to be as follows.
[0015] In a vacuum insulation material in which the core material is vacuum sealed in an outer bag, moisture gradually seeps in through the heat-sealed portion of the outer bag, but in the case of glass fibers with a high ratio A, the glass fibers have a high affinity with water, making it easier for the core material to retain moisture and silanol groups to be generated. The vacuum insulation material of Patent Document 1 uses alkali-containing glass containing a large amount of sodium and potassium components as the glass fibers to enable molding at lower temperatures, which is thought to easily cause deterioration of the insulation performance over the long term. On the other hand, if glass fiber with a ratio A of 11 mass% or less is used, the core material will be less likely to retain moisture, and the deterioration of insulation performance due to the effects of moisture will be suppressed, thereby improving the long-term reliability of the vacuum insulation material.
[0016] From the viewpoint of improving the long-term reliability of the vacuum insulation material, the ratio A is preferably 11 mass% or less, more preferably 6 mass% or less, and further preferably 3 mass% or less. Alkali-free glass that is imparted with melting properties by adding boric acid or the like instead of an alkali component and does not substantially contain Na2O and K2O can also be suitably used. The ratio A of Na2O and K2O contained in the glass fiber can be determined from a known composition analysis of the glass fiber.
[0017] The amount of alkali elution from the glass fiber is preferably 1.9 mL / g or less, more preferably 1 mL / g or less, and even more preferably 0.5 mL / g or less. By using glass fiber with an amount of alkali elution below the upper limit, an increase in thermal conductivity due to moisture penetrating into the vacuum insulation material is easily suppressed. The amount of alkali elution from the glass fiber is measured according to the method described in JIS R3503-1994.
[0018] The thermal expansion coefficient of the glass fiber is preferably 90×10 -7 / ℃ or less, more preferably 80×10 -7 / ℃ or less, more preferably 50×10 -7 / °C or less. If the thermal expansion coefficient of the glass fiber is equal to or less than the upper limit, the initial thermal conductivity is low, resulting in a vacuum insulation material with excellent thermal insulation performance. The mechanism by which the initial thermal conductivity is low is not necessarily clear, but if the thermal expansion coefficient of the glass fiber is equal to or less than the upper limit, the glass fiber is less likely to expand when dried after molding of the core material, and voids are less likely to occur around the glass fiber, which is thought to suppress deterioration of the initial thermal conductivity. The lower limit of the thermal expansion coefficient of the glass fiber is not particularly limited, and can be, for example, 5×10 -7 / °C or more. The thermal expansion coefficient of the glass fiber is measured by the method described in the Examples.
[0019] The Young's modulus of the glass fiber is preferably 50 GPa or more, more preferably 60 GPa or more, and even more preferably 70 GPa or more. If the Young's modulus of the glass fiber is equal to or more than the lower limit, it contributes to improving the strength of the core material. The upper limit of the Young's modulus of the glass fiber is not particularly limited, and may be, for example, 80 GPa or less. The Young's modulus of the glass fiber is measured by a tensile test method.
[0020] The glass constituting the glass fiber may be any glass having a ratio A of not more than the upper limit, and examples thereof include aluminoborosilicate glass, borosilicate glass, and aluminosilicate glass. The glass constituting the glass fiber may be one type alone or two or more types in combination. The glass constituting the glass fiber is preferably one or more types selected from aluminoborosilicate glass, borosilicate glass, and aluminosilicate glass. As the glass fiber, E-glass fiber is particularly preferable.
[0021] The glass fibers contained in the core preferably have a fiber length in the range of 0.1 to 10 mm and a fiber length distribution Lw / Ln of 1.05 or more. This increases the compressive strength of the core, and suppresses the core from being crushed when it is vacuum-sealed in the outer bag. As a result, the vacuum-sealed core is maintained at a low density and has a low thermal conductivity, making it easier to obtain excellent heat insulation performance.
[0022] Ln is the number-average fiber length of the glass fibers, and is calculated from the number-based frequency distribution obtained by measuring the lengths of 50 or more glass fibers randomly in a photograph observed with an optical microscope, using the following formula (3). Lw is the weight-average fiber length of the glass fibers, and is calculated from the weight-based frequency distribution obtained by measuring the lengths of 50 or more glass fibers randomly in a photograph observed with an optical microscope, using the following formula (4). Here, Ni in equations (3) and (4) is the number of fibers in each histogram of the average length Li. A larger Lw / Ln ratio indicates a wider distribution of the fiber lengths of the glass fibers.
[0023]
number
[0024] The fiber length of the glass fibers is preferably in the range of 0.1 to 10 mm. Lw / Ln is preferably 1.05 or more, more preferably 1.10 or more, and further preferably 1.2 or more. The upper limit of Lw / Ln is not particularly limited, and can be, for example, 2.00 or less.
[0025] The fiber length spread index (D90-D10) / D50 of the glass fiber is preferably 0.21 or more, more preferably 0.4 or more, and even more preferably 0.6 or more. If (D90-D10) / D50 is equal to or more than the lower limit, the compressive strength of the core material is likely to be high, and a vacuum insulation material with excellent thermal insulation performance is likely to be obtained. The upper limit of (D90-D10) / D50 is not particularly limited, and can be, for example, 2.0 or less. The larger the (D90-D10) / D50, the wider the distribution of the glass fiber lengths.
[0026] The fiber length D10 of the glass fiber is preferably 2.4 mm or less, more preferably 2.0 mm or less, and further preferably 1.8 mm or less. The fiber length D50 of the glass fiber is preferably 2.0 to 5.0 mm. The fiber length D90 of the glass fiber is preferably 3.0 to 7.0 mm.
[0027] The content of glass fiber in the core material is preferably 2 to 30 mass%, more preferably 2 to 20 mass%, and even more preferably 2 to 15 mass%, based on the total mass of the core material. If the content of glass fiber is equal to or more than the lower limit, a vacuum insulation material having excellent long-term reliability and high compressive strength is likely to be obtained. If the content of glass fiber is equal to or less than the upper limit, an increase in solid heat transfer due to the fiber can be suppressed, and therefore a decrease in insulation performance can be easily suppressed.
[0028] The average aggregate particle size D50 of the fumed silica used in the core material is preferably 5 to 50 μm, more preferably 5 to 30 μm, and further preferably 5 to 20 μm. If D50 is equal to or greater than the lower limit, scattering during the reduced pressure sealing step is easily suppressed. If D50 is equal to or less than the upper limit, solid heat transfer is suppressed, and excellent heat insulating performance is easily obtained.
[0029] The specific surface area of the fumed silica is preferably 50 to 400 m 2 / g, more preferably 100 to 350m 2 / g, more preferably 200 to 300m 2 When the specific surface area of the fumed silica is equal to or greater than the lower limit, excellent heat insulating performance is easily obtained. When the specific surface area of the fumed silica is equal to or less than the upper limit, scattering during the reduced pressure sealing step is easily suppressed. The specific surface area is measured by the nitrogen adsorption method (BET method).
[0030] As an example of fumed silica, Aerosil 200 (specific surface area 200 m 2 / g, manufactured by Nippon Aerosil Co., Ltd.), Aerosil 300 (specific surface area 300 m 2 / g, manufactured by Nippon Aerosil Co., Ltd.), CAB-O-SIL M-5 (specific surface area 200 m 2 / g, manufactured by Cabot Japan Co., Ltd.), CAB-O-SIL H-300 (specific surface area 300 m 2 / g, manufactured by Cabot Japan Co., Ltd.), Leolosil QS30 (specific surface area 300 m 2 Commercially available products such as 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether, manufactured by Tokuyama Corporation) can be used. The core material may contain one type of fumed silica or two or more types of fumed silica.
[0031] The content of fumed silica in the core material is preferably 50 to 90 mass%, more preferably 60 to 90 mass%, and further preferably 70 to 90 mass%, based on the total mass of the core material. If the content of fumed silica is equal to or more than the lower limit, a core material with high strength is easily obtained.
[0032] Examples of the radiation suppressing component include metal particles such as aluminum particles, silver particles, and gold particles, graphite, carbon black, silicon carbide, titanium oxide, tin oxide, and potassium titanate. From the viewpoint of improving thermal conductivity and workability, the radiation suppressing component is preferably one or more selected from graphite, silicon carbide, titanium oxide, tin oxide, and potassium titanate. The radiation suppressing component contained in the core material may be one type or two or more types.
[0033] The content of the radiation-suppressing component in the core material is preferably 3 to 30 mass%, more preferably 5 to 25 mass%, and even more preferably 10 to 20 mass%, based on the total mass of the core material. If the content of the radiation-suppressing component is equal to or higher than the lower limit, deterioration of the thermal conductivity of the vacuum insulation material due to radiation within the core material can be suppressed. If the content of the radiation-suppressing component is equal to or lower than the upper limit, the effect of increasing solid heat transfer due to the radiation-suppressing component can be suppressed, making it easier to obtain excellent heat insulation performance.
[0034] As long as the effect of the present invention is not impaired, materials other than fumed silica, radiation suppression components, and glass fibers may be blended into the core material. Examples of the other materials include binders and porous silica. The other materials contained in the core material may be one type or two or more types. Typical examples of the binder are inorganic binders such as sodium silicate, aluminum phosphate, magnesium sulfate, magnesium chloride, etc., but are not limited thereto, and may be organic binders.
[0035] The shape of the core material is typically flat, but is not limited thereto. The shape of the core material as viewed in the thickness direction can be appropriately designed depending on the application, and examples of the shape include a square, a rectangle, and a circle.
[0036] In order to easily obtain a vacuum insulation material having low thermal conductivity and excellent heat insulation performance, the density of the core material sealed under reduced pressure is preferably 0.30 g / cm. 3 Less than or equal to 0.20 g / cm 3 or less, more preferably 0.18 g / cm 3 If the density of the core material sealed under reduced pressure is equal to or less than the upper limit, the core material can be easily handled, and the fumed silica and the radiation suppressing component are less likely to scatter from the core material during sealing under reduced pressure. In this respect, the density of the core material sealed under reduced pressure is preferably 0.11 g / cm. 3 More than 0.12 g / cm is preferable. 3 More than 0.13 g / cm is preferable. 3The lower and upper limits of the density of the core material sealed under reduced pressure can be arbitrarily combined, and are preferably 0.11 to 0.30 g / cm. 3 , more preferably 0.13 to 0.20 g / cm 3 It is.
[0037] The "density of the core material sealed under reduced pressure" refers to the average density of the entire core material sealed under reduced pressure in the outer bag, and is a value measured by the following measurement method. The core material is placed inside an outer bag and placed in a vacuum chamber equipped with a heat sealing function. With the pressure inside the chamber reduced to 5 Pa, the opening of the outer bag is heat sealed to seal it, and the outside of the outer bag is returned to atmospheric pressure conditions to obtain the vacuum insulation material. The weight of the core material enclosed under reduced pressure is calculated from the weight of the vacuum insulation material and the weight of the outer material. The volume is calculated from the average of the side lengths and thicknesses at five points. The density is calculated from the calculated core material weight and volume.
[0038] In order to easily achieve excellent insulation performance, taking into account the effects of thermal bridges that occur at the ends of the vacuum insulation material, the thickness of the core material is preferably 2 mm or more, more preferably 5 mm or more, and even more preferably 8 mm or more. The "thickness of the core material" means the average thickness of the entire core material. The thickness is measured at any five points in the core material, and the average value is defined as the thickness of the core material.
[0039] (Outer bag) The size and shape of the outer bag are not particularly limited and can be set according to the desired size and shape of the vacuum insulation material. The gas barrier film used for the outer bag is an airtight film, and a typical example is a laminated film having a sealant layer and a barrier layer, but is not limited thereto. The gas barrier film may have other layers such as an adhesive layer, a protective layer, etc. in addition to the sealant layer and the barrier layer.
[0040] The sealant layer is provided as the innermost layer of the gas barrier film. The material forming the sealant layer is not particularly limited, and examples thereof include polyolefin resins such as low-density polyethylene, medium-density polyethylene, linear low-density polyethylene (LLDPE), polypropylene, etc. The material constituting the sealant layer may be one type or two or more types. The sealant layer may have a single layer structure or a multi-layer structure.
[0041] Examples of the barrier layer include an aluminum deposition layer, an aluminum foil layer, and a metal oxide deposition layer made of alumina, silica, or the like. The aluminum deposition layer and the metal oxide deposition layer can be formed by depositing aluminum or a metal oxide onto a deposition substrate. The deposition substrate can be a resin film such as a polyethylene terephthalate (PET) film or an ethylene-vinyl alcohol copolymer (EVOH) film. The number of barrier layers in the gas barrier film is preferably 2 or more, more preferably 2 to 6, and further preferably 2 to 4.
[0042] The adhesive used in the adhesive layer is preferably an adhesive suitable for dry lamination, such as a two-component curing polyurethane adhesive, an acrylic adhesive, or an epoxy adhesive, and is particularly preferably a two-component curing polyester adhesive.
[0043] The protective layer is preferably provided on the outermost layer, but is not limited thereto, and may be provided between the barrier layer and the sealant layer, or between two barrier layers. When the gas barrier film has a protective layer, the protective layer may be one layer or two or more layers.
[0044] Examples of materials for forming the protective layer include polyamide resins such as nylon 6, nylon 66, and copolymers of nylon 66 and nylon 6, and polyester resins such as PET and polyethylene naphthalate.
[0045] The thickness of the gas barrier film is preferably 40 to 65 μm, more preferably 45 to 65 μm, and further preferably 47 to 62 μm. When the thickness of the gas barrier film is equal to or greater than the lower limit, the film strength is excellent. When the thickness of the gas barrier film is equal to or less than the upper limit, the weight of the vacuum insulation material can be reduced.
[0046] When a flat vacuum insulation material is produced and a pressure of 4400 Pa is applied to the plane in the thickness direction of the vacuum insulation material for one hour, the amount of strain is preferably 0.25% or less, more preferably 0.23% or less, and even more preferably 0.20% or less. If the amount of strain is equal to or less than the upper limit, the decrease in thermal conductivity is suppressed, and the insulation performance is excellent.
[0047] The degree of vacuum inside the outer bag of the vacuum insulation material is preferably 1×10 to obtain excellent insulation performance and to extend the life of the vacuum insulation material. 3 Pa or less, more preferably 5×10 2 Pa or less, more preferably 3×10 2 From the viewpoint of facilitating decompression inside the outer bag, the degree of vacuum inside the outer bag is preferably 1 Pa or more, and more preferably 10 Pa or more.
[0048] The total thickness of the vacuum insulation material is preferably 3 mm or more, more preferably 5 mm or more, and even more preferably 10 mm or more. The total thickness of the vacuum insulation material is preferably 40 mm or less, and more preferably 30 mm or less. The "total thickness of the vacuum insulation material" refers to the thickness of the portion excluding the edge folds (folded-back portions) at the ends of the gas barrier film.
[0049] [Vacuum insulation material manufacturing method] The method for producing the vacuum insulation material according to the embodiment is not particularly limited except for using glass fibers having a ratio A of 11 mass% or less, and any known production method can be used. For example, there is a method including press-molding a raw material mixture containing fumed silica, a radiation suppression component, and glass fibers to obtain a core material, and vacuum-sealing the core material in an outer bag formed of a gas barrier film.
[0050] When using glass fibers having a fiber length in the range of 0.1 to 10 mm and a fiber length distribution Lw / Ln of 1.05 or more, examples of the method include a method of pulverizing a part of glass fibers having a fiber length of 1.5 to 10 mm with a pulverizing device such as a ball mill to broaden the fiber length distribution, a method of mixing two or more glass fibers having different fiber lengths in the range of 0.1 to 10 mm to obtain a fiber mixture having a wide fiber length distribution, and a method of pulverizing a part of the fiber mixture with a pulverizing device. While pulverizing the glass fibers with the pulverizing device, glass fibers having the same fiber length may be sequentially fed into the pulverizing device. When a ball mill is used, the pulverization treatment time is preferably 1 to 10 hours, and more preferably 2 to 5 hours.
[0051] The method for obtaining a raw material mixture containing fumed silica, a radiation suppressing component, and glass fibers is not particularly limited, and examples thereof include a method using a V-type mixer, a blender equipped with an agitator, or the like.
[0052] For press molding of the raw material mixture, for example, a manufacturing device for insulating boards described in paragraphs 0013 to 0028 of JP 2016-102511 A can be used. The manufacturing device includes an upper mold having a convex portion with a reduced pressure chamber formed therein, and a lower mold having a concave portion, and a plurality of exhaust holes are formed on the surface of the convex portion on the side of the concave portion. With the raw material mixture being poured into the concave portion of the lower mold, the upper mold is lowered by a cylinder, the convex portion of the upper mold is fitted into the concave portion of the lower mold, and the reduced pressure chamber of the upper mold is reduced by a vacuum pump, thereby performing press molding while exhausting air from the raw material mixture. The thickness and density of the core material can be controlled by adjusting the amount of raw material mixture poured into the concave portion of the lower mold and the pressing pressure.
[0053] After press molding, it is preferable to heat-treat and dry the core material, which can sufficiently remove moisture contained in the raw material and further reduce the thermal conductivity of the core material. The method for heat treating the core material is not particularly limited, and examples thereof include a method of heating in a constant temperature dryer, an electric furnace, or the like. The heat treatment temperature is preferably 80 to 200°C, and more preferably 100 to 200°C. The heat treatment time is preferably 1 to 120 hours, more preferably 1 to 60 hours.
[0054] The method for vacuum-sealing the core material inside the outer bag is not particularly limited, and examples include a method in which the core material is stored inside the outer bag, the opening of the outer bag is sealed under reduced pressure conditions, and then the outside of the outer bag is returned to atmospheric pressure conditions.
[0055] In one example, a core material is placed inside an outer bag made by overlapping two gas barrier films and sealing three sides, and the bag is placed inside a vacuum chamber equipped with a heat seal function, and the inside of the vacuum chamber is depressurized. After the inside of the vacuum chamber is depressurized to a predetermined pressure, the remaining open side of the outer bag is heat sealed to seal the bag, and the inside of the vacuum chamber is returned to atmospheric pressure. In another example, after the core material is housed in the outer bag, the air inside the outer bag may be sucked out to reduce the pressure inside the outer bag, and the outer bag may be sealed by heat sealing or the like.
[0056] The core material may be housed in an inner bag having air permeability and then sealed in an outer bag under reduced pressure. The inner bag may be any material that is breathable and prevents the raw material from leaking out when the core material is sealed under reduced pressure, and examples of the inner bag include bags made of paper, nonwoven fabric, etc.
[0057] As described above, the vacuum insulation material of the embodiment has excellent long-term reliability because the core material is made of glass fiber with a ratio A of 11 mass% or less, which suppresses a gradual increase in the thermal conductivity of the core material due to moisture that has penetrated into the vacuum insulation material. EXAMPLES
[0058] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following descriptions. In the following examples, Examples 1 and 3 to 7 are working examples, and Examples 2 and 8 to 9 are comparative examples.
[0059] [Fiber length D10, D30, D50, D90] In a photograph of the fibers observed with an optical microscope, the lengths of 50 or more randomly selected fibers were measured, and a cumulative number distribution curve was obtained in which the total number of fibers in the fiber length distribution calculated based on the number of fibers was set to 100%. The fiber lengths at which the cumulative number was 10%, 30%, 50%, and 90% were determined as D10, D50, and D90, respectively.
[0060] [Average fiber length] In a photograph of the fibers observed under an optical microscope, the lengths of 50 or more randomly selected fibers were measured, and the average value was taken as the average fiber length of the fibers.
[0061] [Ln and Lw] In a photograph of the fibers observed under an optical microscope, the lengths of 50 or more randomly selected fibers were measured, and Ln was calculated from the number-based frequency distribution using formula (3) above. Also, Lw was calculated from the weight-based frequency distribution using formula (4) above. Here, Ni in formulas (3) and (4) is the number of fibers in each histogram of the average length Li.
[0062]
number
[0063] [Density of the core material sealed under reduced pressure] The weight of the core material sealed in at reduced pressure was calculated from the weight of the vacuum insulation material and the weight of the exterior material. The volume was calculated from the average value of the side length and thickness at five points. The density was calculated from the calculated core material weight and volume.
[0064] [Alkaline elution amount] The amount of alkali elution from the glass fiber was measured according to the method described in JIS R3503-1994.
[0065] [Thermal expansion coefficient] The thermal expansion coefficient of the glass fiber was measured in the temperature range of 50 to 400° C. at a heating rate of 5° C. / min using a thermomechanical analyzer (TMA).
[0066] [Compressive strength (amount of strain)] Each example of vacuum insulation material was placed on a horizontal surface, and a 10 kg weight was placed on the top surface in an area of 150 mm x 150 mm, and a pressure of approximately 4400 Pa was applied for one hour. The thickness displacement after applying a pressure of approximately 4400 Pa was measured, and the amount of strain (%) was calculated.
[0067] [Moisture content of core material] The moisture content of the core material was measured by the Karl Fischer liquid constant method.
[0068] [Thermal Conductivity] The thermal conductivity of the vacuum insulation material was measured using a thermal conductivity measuring device HFM-436 (NETZSCH). Three samples were prepared and measured, and the average value was taken as the thermal conductivity of the vacuum insulation material. The measurement conditions were a center temperature of 25°C and a temperature difference of 20°C. The thermal conductivity measured for the vacuum insulation material before the long-term reliability test described below was defined as the "initial thermal conductivity."
[0069] [Long-term reliability] A long-term reliability test was conducted in which the vacuum insulation material obtained in each example was left to stand in an environment of 70°C and 90 RH% for 28 days. The thermal conductivity, internal pressure, and mass of the vacuum insulation material were measured before and after the long-term reliability test, and the respective increases were calculated.
[0070] [Core material raw materials] Fumed silica 1 (average agglomerated particle size D50: 13.5 μm) Fiber 1: E-glass fiber (fiber diameter 6.5 mm) with a fiber length of 3 mm was ground for 15 minutes using a blender with an agitator (fiber length range: 0.2-3 mm). Fiber 2: Glass wool (soda-lime glass, fiber diameter 6 mm) with a fiber length of 3 mm was ground for 15 minutes using a blender with an agitator (fiber length range: 0.2 to 3 mm). Fiber 3: E-glass fiber with a fiber length of 3 mm was ground for 10 minutes using a blender with an agitator (fiber length range: 0.3 to 3 mm). Fiber 4: E-glass fiber with a fiber length of 6 mm was ground for 10 minutes using a blender with an agitator (fiber length range: 0.5-6 mm). Fiber 5: E-glass fiber with a fiber length of 3 mm and E-glass fiber with a fiber length of 6 mm were mixed in a mass ratio of 90:10 and ground for 10 minutes using a blender with an agitator (fiber length range: 0.5-6 mm). Fiber 6: E-glass fiber with a fiber length of 3 mm and E-glass fiber with a fiber length of 6 mm were mixed in a mass ratio of 50:50 and ground for 10 minutes using a blender with an agitator (fiber length range: 0.3 to 6 mm). Fiber 7: E-glass fiber with a fiber length of 3 mm and E-glass fiber with a fiber length of 6 mm were mixed in a mass ratio of 30:70 and ground for 10 minutes using a blender with an agitator (fiber length range: 0.3 to 6 mm). Fiber 8: E-glass fiber with a fiber length of 3 mm was ground for 1 minute using a blender with an agitator (fiber length range: 2.3 to 3 mm). Fiber 9: Silica-magnesia-calcia fiber (product name "Superwool (registered trademark) Plus) bulk, D30: 227 μm, D90: 902 μm, average fiber diameter: 3 μm, manufactured by Shin-Nihon Thermal Ceramics Co., Ltd.) Radiation suppression component 1: Graphite
[0071] [Example 1] 80 parts by mass of fumed silica 1, 16 parts by mass of radiation suppression component 1, and 4 parts by mass of fiber 1 were mixed, and the raw material mixture was press-molded and heat-treated at 200°C for 1 hour to produce a flat core material measuring 200 mm in length, 200 mm in width, and 15 mm in thickness. The fiber diameter, fiber length, ratio A, alkali elution amount, thermal expansion coefficient, and core material moisture content of fiber 1 are shown in Table 1. The three sides of two 300mm x 300mm gas barrier films were heat-sealed to create a three-sided sealed outer bag, a core material was placed inside the outer bag, and the bag was placed in a vacuum chamber equipped with a heat seal function. The pressure inside the chamber was then reduced to 5 Pa, and the opening of the outer bag was heat-sealed to seal it in that state, and the outside of the outer bag was returned to atmospheric pressure to obtain a vacuum insulation material. The measurement results of the compressive strength and initial thermal conductivity of the obtained vacuum insulation material, as well as the evaluation results of long-term reliability are shown in Table 1.
[0072] [Example 2] A vacuum insulation material was produced in the same manner as in Example 1, except that the glass fibers used were changed as shown in Table 1. The fiber diameter, fiber length, ratio A, alkali elution amount, thermal expansion coefficient, and core moisture content of fiber 2 are shown in Table 1. The measurement results of compressive strength and initial thermal conductivity, and the evaluation results of long-term reliability of the obtained vacuum insulation material are also shown in Table 1.
[0073] [Table 1]
[0074] As shown in Table 1, the vacuum insulation material of Example 1, which used glass fiber with a ratio A of 11 mass% or less, had smaller increases in thermal conductivity, internal pressure, and mass in the long-term reliability test and was superior in long-term reliability compared to the vacuum insulation material of Example 2, which used glass fiber with a ratio A of more than 11 mass%.
[0075] [Example 3] 80 parts by mass of fumed silica 1, 16 parts by mass of radiation-suppressing component 1, and 4 parts by mass of fiber 3 were mixed, and the raw material mixture was press-molded and heat-treated at 200°C for 1 hour to produce a flat core material with length 200 mm x width 200 mm x thickness 15 mm. The measurement results of D10, D30, D50, D90, (D90-D10) / D50, average fiber length, Ln, Lw, and Lw / Ln of fiber 3 are shown in Table 2. The three sides of two 300 mm x 300 mm gas barrier films were heat-sealed to prepare a three-sided sealed outer bag, a core material was placed inside the outer bag, and the bag was placed in a vacuum chamber equipped with a heat seal function. The pressure inside the chamber was then reduced to 5 Pa, and the opening of the outer bag was heat-sealed in this state to seal the bag, and the outside of the outer bag was returned to atmospheric pressure to obtain a vacuum insulation material.
[0076] [Examples 4-9] A vacuum insulation material was produced in the same manner as in Example 3, except that the fibers used were changed as shown in Table 2.
[0077] [Table 2]
[0078] The density, compressive strength (amount of strain), and thermal conductivity of the core material sealed under reduced pressure for the vacuum insulation materials of Examples 3 to 9 were measured and the results are shown in Table 3. Furthermore, the frequency distribution based on the number of fibers versus fiber length (mm) for Fiber 6 used in Example 6 and Fiber 8 used in Example 8 is shown in Figure 2.
[0079] [Table 3]
[0080] As shown in Table 3, the vacuum insulation materials of Examples 3 to 7, which used fibers 3 to 7 with an Lw / Ln of 1.05 or more, had smaller strain, higher compressive strength, lower thermal conductivity, and superior insulation performance than the vacuum insulation materials of Examples 8 to 9, which used fibers 8 to 9 with an Lw / Ln of less than 1.05. 2, Fiber 6 used in Example 6, which had an Lw / Ln of 1.05 or more, had a wider fiber length distribution than Fiber 8 used in Example 8, which had an Lw / Ln of less than 1.05. From these findings, it is believed that the use of fibers with a wider fiber length distribution increased the compressive strength and improved the thermal insulation performance. [Explanation of symbols]
[0081] 1. Vacuum insulation material 10 Core material 12 Outer bag
Claims
1. A vacuum insulation material comprising a core material and a gas barrier film covering the core material, the core material being vacuum sealed in an outer bag formed of the gas barrier film, the core material comprises fumed silica, a radiation suppressing component, and glass fibers; The Na contained in the glass fiber 2 O and K 2 A vacuum insulation material, wherein the ratio of the total mass of O to the total mass of the glass fibers is 11 mass% or less.
2. The vacuum insulation material according to claim 1 , wherein the glass fiber has an alkali elution amount of 1.9 mL / g or less.
3. The thermal expansion coefficient of the glass fiber is 90×10 -7 The vacuum insulation material according to claim 1 or 2, wherein the temperature is 0.15 to 1.5° C. or less.
4. The vacuum insulation material according to claim 1 or 2, wherein the glass fiber has a Young's modulus of 50 GPa or more.
5. 3. The vacuum insulation material according to claim 1, wherein the glass constituting the glass fibers is at least one type selected from the group consisting of aluminoborosilicate glass, borosilicate glass, and aluminosilicate glass.
6. With respect to the total mass of the core material, the content of the fumed silica is 50 to 90 mass%, the content of the radiation suppression component is 3 to 30 mass%, and the content of the glass fiber is 2 to 30 mass%, The density of the core material sealed under reduced pressure is 0.30 g / cm 3 is as follows: The glass fibers have a fiber length in the range of 0.1 to 10 mm; 3. The vacuum insulation material according to claim 1, wherein a fiber length distribution Lw / Ln, which is expressed as a ratio of the number average fiber length Ln to the weight average fiber length Lw of the glass fibers, is 1.05 or more.
7. The vacuum insulation material according to claim 6, wherein the fiber length D10 of the glass fibers is 2.4 mm or less.
8. The fiber length spread index (D90-D10) / D50 of the glass fiber, which is expressed by the difference between the fiber length D90 and the fiber length D10 with respect to the fiber length D50 of the glass fiber, is 0.21 or more. Vacuum insulation material according to claim 6.
9. The vacuum insulation material according to claim 6, wherein the radiation suppressing component is at least one selected from the group consisting of graphite, silicon carbide, titanium oxide, tin oxide, and potassium titanate.
10. The vacuum insulation material according to claim 6, wherein when a flat vacuum insulation material is produced and a pressure of 4400 Pa is applied to a plane in the thickness direction of the vacuum insulation material for one hour, the amount of distortion is 0.25% or less.
Citation Information
Patent Citations
Vacuum heat insulation material
JP2008215538A